Asymptotic analysis of the laminar viscous flow over a porous bed - Jäger, Willi; Mikelić, Andro; Neuß, Nicolas (SIAM journal on scientific computing, 2001)
We consider the laminar viscous channel flow over a porous surface. The size of the pores is much smaller than the size of the channel, and it is important to determine the effective boundary conditions at the porous surface. We study the corresponding boundary layers, and, by a rigorous asymptotic expansion, we obtain Saffman’s modification of the interface condition observed by Beavers and Joseph.